2016
DOI: 10.4103/0970-9290.183133
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three diagnostic techniques for detecting occlusal dental caries in primary molars: An in vivo study

Abstract: This study showed low sensitivity but substantial specificity with visual inspection. Bitewing radiography performed poorly overall when compared with the other two systems. The CarieScan PRO technique gave the highest overall combination of sensitivity and specificity for detection of occlusal caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the study where the diagnosis of occlusal caries of primary teeth was compared with a visual inspection, bitewing radiography, and Cariescan Pro, it was reported that the sensitivity and specificity of Cariescan Pro were high. 60…”
Section: Electrical Conductivity Measurementsmentioning
confidence: 99%
“…In the study where the diagnosis of occlusal caries of primary teeth was compared with a visual inspection, bitewing radiography, and Cariescan Pro, it was reported that the sensitivity and specificity of Cariescan Pro were high. 60…”
Section: Electrical Conductivity Measurementsmentioning
confidence: 99%
“…Observation with DOM ne through direct observation, but there is not much data regarding the advantages of the DOM in pediatric dental medicine. [22][23][24] A group of authors conducted a study regarding the role of magnification in the early diagnosis of carious lesions by comparing the clinical diagnoses of 299 occlusal surfaces, examined directly and with the aid of a DOM. They found that the diagnoses differed most frequently for teeth that were assessed as healthy during direct observation, but were found to have a carious lesion, when observed under magnification.…”
Section: Observation Without Magnificationmentioning
confidence: 99%